ARF6s Identification and Function Analysis Provide Insights Into Flower Development of Punica granatum L. - Zhao, Yujie; Wang, Yuying; Zhao, Xueqing; Yan, Ming; Ren, Yuan; Yuan, Zhaohe (Frontiers in Plant Science, 2022)
Based on the genome and small-RNA sequencing of pomegranate, miRNA167 and three target genes PgARF6 were identified in ‘Taishanhong’ genome. Three PgARF6 genes and their corresponding protein sequences, expression patterns in pomegranate flower development and under exogenous hormones treatments were systematically analyzed in this paper. We found that PgARF6s are nuclear proteins with conserved structures. However, PgARF6s have different protein structures and expression profiles in pomegranate flower development. At the critical stages of pomegranate ovule sterility (8.1–14.0 mm), the expression levels of PgARF6s in bisexual flowers were lower than those in functional male flowers. Interestingly, PgARF6c expression level was significantly higher than PgARF6a and PgARF6b. Under the treatment of exogenous IBA and 6-BA, PgARF6s were down-regulated, and the expression of PgARF6c was significantly inhibited. PgmiR167a and PgmiR167d have a binding site on PgARF6 genes sequences, and PgARF6a has the direct targeted regulatory relationship with PgmiR167a in pomegranate. At the critical stage of ovule development (8.1–12.0 mm), exogenous IBA and 6-BA promoted the content of GA and ZR accumulation, inhibited BR accumulation. There was a strong correlation between the expression of PgARF6a and PgARF6b. Under exogenous hormone treatment, the content of ZR, BR, GA, and ABA were negatively correlated with the expressions of PgARF6 genes. However, JA was positively correlated with PgARF6a and PgARF6c under IBA treatment. Thus, our results provide new evidence for PgARF6 genes involving in ovule sterility in pomegranate flowers.